Influence of Women Empowerment on Community Development in Ilorin Metropolis, Kwara State, Nigeria - Okoji, Olufemi Onweazu; Amidat, Abdullahi (Papers in Education and Development, 2022)
This paper examines the influence of women empowerment on community development. The study was conducted in Metropolis, Kwara state in Nigeria. The population for this study comprised of all women in Ilorin Metropolis. A total of 300 women were sampled using simple random sampling technique. Questionnaire with a reliability coefficient of 0.85 was used for data collection while the data collected were analyzed using inferential statistics of a linear multiple regression to test the hypothesis postulated at 0.05 level of significance. Findings revealed that, the combination of the independent variables significantly predicted the dependent variable (F(3, 296) = 9.370, p<0.05). It was recommended in this study that government and non-government organizations should periodically empower women through the provision of financial assistants and health facilities. Keywords: community development., healthy living, human capital, participation, women empowermen